Effect of Azimuthal Asymmetry Caused by Upwelling on 3D Ocean Acoustic Propagation - Raju, R. P.; Anand, P.; Fernandez, Dominic Ricky; Rao, A. Raghunadha (Defence Science Journal, 2019)
3-D underwater parabolic equation model based on implicit finite difference method has been implemented for South Eastern Arabian Sea (SEAS). The bathymetric and geo-acoustic features have been integrated in the model for a 50 km circular region in SEAS. The model can simulate the effects of azimuthal variation in oceanographic features and compute azimuthally coupled pressure due to an omni-directional source. The azimuthal variation in oceanographic conditions can be observed during an upwelling event. In the first case study, the effect of upwelling event on three-dimensional acoustic propagation has been studied by using sound speed profile data derived from INS Sagardhwani observations. The difference in Transmission loss mosaic for upslope and downslope propagation is due to bathymetry as well as upwelling. In the second case study, the effect of upwelling only, is studied by running a model corresponding to range independent sound speed profile field and range dependent bathymetry. It was observed that during this upwelling event, the transmission loss is higher at longer ranges during upslope propagation than downslope propagation. This is due to the increase in the thickness of sonic layer duct as acoustic wave propagates from shallow to deep water. The effect of azimuthal variation i